Avaliação da atividade tóxica, genotóxica e antigenotóxica de hymenaea courbaril l. em camundongos e drosophila melanogaster - Vale, Camila Regina do (2012)
Hymenaea courbaril L. (Family Fabaceae), popularly known in Brazil as jatobá, is a tropical species that occurs in semi-deciduous forest of the South America. The species has been used in Brazil for culinary purposes and in folk medicine to treat arthritis, gastric dysfunction, inflammation and respiratory diseases. Due to the spreading use of this plant as a therapeutic resource and food, the present study aimed to evaluate the toxic, genotoxic, recombinogenic and antigenotoxic effects of Hymenaea courbaril sap (Hycs) using the mouse bone marrow micronucleus test and somatic mutation and recombination test (SMART) in Drosophila melanogaster. To evaluate the clastogenic and aneugenic activities by micronucleos test the animals were treated with 3 concentrations of Hycs (5, 10 and 15 mL/kg body weight). To evaluate the anti-clastogenic and anti-aneugenic activities, the animals were simultaneously treated with Hycs and mitomycin C (4mg/kg body weight). To evaluate the mutagenic and recombinogenic activities by SMART, three-day-old larvae derived from standard (ST) and high bioactivation (HB) crosses were treated with 3 doses of Hycs (0.3, 1.5 or 3 mL) for approximately 48 hours. To evaluate the antimutagenic and antirecombinogenic activities, larvae derived from both crosses were cotreated with 3 doses of Hycs (0.3, 1.5 or 3 mL) and doxorubicin (0.125 mg/mL). Our results in the mouse bone marrow micronucleus test showed that SHyc exhibited no cytotoxic, clastogenic and/or aneugenic effects, but showed anticytotoxic, anti-clastogenic and /or anti-aneugenic activities in mouse bone marrow. The results for the SMART test showed no mutagenic and recombinagenic effects, but antimutagenic and anti-recombinogenic activities were found in both crosses in somatic cells of Drosophila melanogaster.